Systemic Lupus Erythematosus with Lupus Nephritis, Community-Acquired Pneumonia, Bilateral Pleural Effusion, Pericardial Effusion, and Hypoalbuminemia in a 20-Year-Old Male Patient: A Case Report - Pratama Yudha, Muhammad Agung; Deka Viotra; Najirman (HM Publisher, 2024)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem inflammation. Lupus nephritis is a serious complication of SLE that can cause kidney failure. Community acquired pneumonia (CAP), bilateral pleural effusion, pericardial effusion, and hypoalbuminemia are other complications that can occur in SLE patients. Case presentation: We report the case of a 20-year-old man with SLE who presented with lupus nephritis, CAP, bilateral pleural effusion, pericardial effusion, and hypoalbuminemia. Patients were diagnosed with SLE based on the American College of Rheumatology (ACR) classification criteria. The diagnosis of lupus nephritis is made based on the presence of proteinuria, hematuria, and casts on urinalysis, as well as findings on kidney biopsy. CAP is diagnosed based on the presence of fever, cough, cough with phlegm, and infiltrates on chest X-ray. Bilateral pleural effusion and pericardial effusion were diagnosed based on physical examination and findings on chest ultrasound. Hypoalbuminemia is diagnosed based on low serum albumin levels. Patients are treated with steroids, antimalarials, diuretics, and antibiotics. The patient's symptoms improved and complications resolved. Conclusion: SLE is a complex disease that can cause a variety of serious complications. Early diagnosis and treatment of these complications are essential to improve the patient's prognosis. This case shows that SLE can cause a variety of serious complications, including lupus nephritis, CAP, bilateral pleural effusion, pericardial effusion, and hypoalbuminemia. Early diagnosis and treatment of these complications are essential to improve the patient's prognosis.